Use of Bioremediation with Microbes for Industrial Waste Management - Tri Putri Wahyuni; Atyka Trianisa (CV. Get Press Indonesia, 2025)
Rapid industrial growth has significantly contributed to environmental pollution, particularly through hazardous waste disposal. Industrial waste, including heavy metals and toxic organic compounds, poses a major challenge for sustainable environmental management. Improper management of this waste can lead to contamination of water, soil, and air, threatening human health and ecosystems (Bagaskara, 2023; Supraptini, 2002). This study investigates the potential of bioremediation using microbes for industrial waste management and identifies factors influencing its effectiveness. Conducted as an experimental laboratory study, the research tests various microorganisms known for their bioremediation capabilities, such as Pseudomonas, Bacillus, and Aspergillus.Analysis of contaminated soil revealed lead (Pb) levels at 63.1 mg/kg, exceeding the livestock toxic limit of 10–30 mg/kg. The growth index (GI) for the inoculum treatment increased by 84.3% to 136.7% over a sixty-day incubation period, while the control treatment showed minimal changes (88.8% to 111.7%). These findings indicate that optimal incubation conditions and appropriate microbial selection can enhance soil quality, making it safer for plant growth and less harmful to the environment. Expanding bioremediation practices could significantly mitigate the adverse effects of industrial waste on environmental pollution. Overall, this research highlights the viability of microbial bioremediation as an effective strategy for managing industrial waste and improving ecological health.